Screening for Psychiatric Comorbidities and Psychotherapeutic Assessment in Inpatient Epilepsy Care: Preliminary Results of an Implementation Study - Michaelis, Rosa; Schlömer, Sabine; Lindemann, Anja; Behrens, Vanessa; Grönheit, Wenke; Pertz, Milena; Rammé, Stephanie; Seidel, Sabine; Wehner, Tim; Wellmer, Jörg; Schlegel, Uwe; Popkirov, Stoyan (Frontiers in Integrative Neuroscience, 2021)
Anxiety and depression remain underdiagnosed in routine clinical practice in up to two thirds of epilepsy patients despite significant impact on medical and psychosocial outcome. Barriers to adequate mental health care for epilepsy and/or PNES include a lack of integrated mental health specialists and standardized procedures. This naturalistic study outlines the procedures and outcome of a recently established psychotherapeutic service. Routine screening included the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E, cut-off > 13) and Generalized Anxiety Disorder scale (GAD-7, cut-off > 5). Positively (above cut-off in at least one questionnaire) screened patients were seen for a standardized interview for mental health disorders and the development of a personalized treatment plan. PNES patients were seen irrespective of their screening score. Resources were provided to support self-help and access to psychotherapy. Patients were contacted one month after discharge to evaluate adherence to therapeutic recommendations. 120 patients were screened. Overall, 56 of 77 positively screened patients (77%) were found to have a psychiatric diagnosis through standardized interview. More epilepsy patients with an anxiety disorder had previously been undiagnosed compared to those with a depressive episode (63% vs. 30%); 24 epilepsy patients (62%) with a psychiatric comorbidity and 10 PNES patients (59%) were not receiving any mental health care. At follow-up, 16/17 (94%) epilepsy patients and 7/7 PNES patients without prior psychiatric treatment were adhering to therapeutic recommendations. Integrating mental health specialists and establishing standardized screening and follow-up procedures improve adherence to mental health care recommendations in epilepsy and PNES patients.